USING OF REALIA IN TEACHING PROCESS - Satniyazovna, Toreniyazova Ziuarkhan (Journal of Higher Education and Academic Advancement, 2024)
The article is defined by the concrete results of the research that is translation of realia from English into Uzbek and vice versa. The translation of realia is one of great and important problems of transference of national and historical peculiarities, which ascend to the very conception of theory of translation as independent discipline. Not setting ourselves a target to give a historical survey we bring only some facts and names connected with the elaboration of this problem in translation. The results can be used in the lectures of translation, lexicology, and stylistics and in practical lessons of English. The aim of this article is to give a complete and through description of the realia and work out the ways of transferring them in the process of translation.